PENGEMBANGAN DAYA TARIK WISATA SUNGAI DI KOTA DENPASAR MELALUI PEMBERDAYAAN MASYARAKAT (STUDI KASUS SUNGAI LOLOAN DI KAWASAN MERTASARI, SANUR KAUH) - Ni Nyoman Sri Wisudawati (Jurnal Ilmiah Hospitality Management, 2017)
Rivers in urban areas are vulnerable gets damage and pollution. River side in urban area are strategic locations as residential areas. The existence of demands on the fulfillment of urban facilities and the high needs of the population as well as limited urban land raises the number of people in urban areas, especially the city of Denpasar who lives in the river side. Along with the development of the city and the unspecified urban environment especially the river side area there will be an impact on the environment, especially in the river flow. Denpasar city government currently has implemented the river revitalization program in Denpasar city by improving the view and cleanliness of the river as utilize the river one of the tourist attraction at Denpasar. One of the rivers in Denpasar that has been laid out is the Loloan river which is located in the Mertasari area Sanur Kauh. This river has a tourism potential that can be developed especially supported by the participation of surrounding communities. This research uses descriptive qualitative method through purposive sampling. SWOT analysis used for reference in the development of tourist attraction at Loloan river. This research is expected to give contribution for stakeholder and government of Denpasar city especially in development of river tourism in Denpasar city area in general and Loloan river in particular.